Current Cataract Surgical Techniques - Wang, Xiaogang (IntechOpen, 2021)
The first clinical application of the phacoemulsification cataract surgical technique (often referred to as "phaco") was introduced in 1967 by Dr. Charles Kelman. This innovation is a big step forward for cataract surgery. With the development of intraocular lens (IOL) design, more and more premium presbyopia- and astigmatism-correction IOLs are being used in clinics. This progress has greatly improved the visual quality of cataract patients. This book discusses the basic surgical skills required to perform this procedure, premium IOL surgical design, specific surgical plans for clinically challenging cases, and more. It provides readers with a comprehensive knowledge of the current state of the art of cataract surgery and surgical design.